She took off her wings and shoes: poems - Bishop, Suzette Marie, author; Utah State University Press, publisher (Colorado State University. Libraries, 2003)
Suzette Marie Bishop teaches writing at Texas A & M International University. This will be her first full-length book, though she's published a chapbook and many individual poems in national poetry journals. Nominated twice for the Pushcart Prize, Ms. Bishop's credits include publications in Antioch Review, 13th Moon, Eratica, Aries, The Little Magazine, and many other literary journals. As a poet and writing teacher on the faculty of Texas A & M International, she gives many readings, as well as workshops for gifted children, seniors, and other writers on the US-Mexico border she has worked with at-risk youth and with the rural Hispanic community.
Foreword / Alicia Ostriker -- 1. Do Not Drive into Smoke. Reaching for Your Hair -- Disruptions -- Elegant Shrimp in Champagne Sauce -- My Dream House -- House-Sitting -- Knowing Objects Will Outlast Them -- My Gown is a Momentary Outline -- Dragons -- The Bat -- One Summer -- Exit Interview -- Melinda -- Horrorscope -- Graveyard -- Visiting Relatives -- Mirror and Sword Trick -- In the Holy Spirit Research Center -- Least Terns -- Bloodstone -- Water Moccasin -- Anasazi Bowl -- Do Not Drive into Smoke -- Wedding Triptych -- Cool Wagons & Bone Chandeliers -- Through the Corridor -- Departing Iceland -- 2. As Good There as Here to Burn. At the Ramada Inn with Ruth and Esther -- Emitting a Sound -- Conversation with Anne Truitt -- The Conservator -- Purple Gloxinia -- Hannah Höch -- Beneath Eva Hesse's Fiberglass Veil -- Photograph of Edna St. Vincent Millay -- Sor Juana Inés de la Cruz -- The Ghost of Christina Rossetti -- As Good There as Here to Burn -- 3. She Took Off Her Wings and Shoes -- She Took Off Her Wings and Shoes (a long poem).
Keywords: American poetry; Poetry -- Collections